The genus Acicula W. Hartmann, 1821 in the Caucasus (Gastropoda: Caenogastropoda: Aciculidae) - Páll-Gergely, Barna; Mumladze, Levan; Grego, Jozef; Giokas, Sinos (Zootaxa, 2023)
The Aciculidae is a family of terrestrial operculate snails with a western Palaearctic distribution. Historically three Acicula species were reported from the Caucasus Mountains, which represents the eastern edge of the family's distribution: A. limbata, A. moussoni and A. parcelineata, all from a few localities. We examined extensive material from the entire range of the Caucasus Mountains by means of classic morphology-based taxonomy and geometric morphometries. We arrived at the following conclusions: (1) At least three species inhabit the Caucasus Mountains, two of which are problematic taxonomically and regarding their nomenclature. (2) The two syntypes of A. moussoni have been lost, and both lectotype designations by the former authors were invalid. Therefore, we designate a neotype for A. moussoni. (3) Acicula limbata was described from Lower Miocene deposits of the Czech Republic. Although the fossil Central European and extant Caucasian shells differ only slightly from one another, it is highly unlikely that they would belong to the same species. Therefore, we suggest using A. limbata only for the Czech fossil species and A. moussoni for the Caucasian extant species. (4) In multiple samples, the generally smaller Acicula parcelineata was found syntopic with the generally larger A. moussoni. Therefore, the two are possibly distinct species. However, it is very difficult to distinguish, and the problem of A. moussoni and A. parcelineata needs further attention. (5) A species with a bullet (or torpedo)-shaped shell and an opisthocline apertural profile from the northern Caucasus region has been treated as A. moussoni by previous authors, but it is distinct from the other two Acicula species by consistent conchological characters and was also found with them in syntopy, and is described here as Acicula telum Páll-Gergely, n. sp.